Sensitive voltammetric method for the fast analysis of the antioxidant pyrogallol using a boron-doped diamond electrode in biofuels. - Chýlková, Jaromíra; Tomášková, Markéta; Janíková, Lenka; Šelešovská, Renáta; Navrátil, Tomáš; Chudobová, Petra (My University, 2017)
A sensitive voltammetric method for the determination of pyrogallol (PY) was developed employing a boron-doped diamond electrode (BDDE). The composition of the supporting electrolyte was investigated during the development of the methodology. Linear sweep voltammetry (LSV) under the optimized experimental conditions was applied for PY determination with a limit of detection and limit of quantiﬁcation of 0.85 and 2.82 lmol L-1, respectively. These values are satisfactory for application to real samples. The usability of this method for the quantiﬁcation of pyrogallol was in range from 2.82 to 296.00 lmol L-1. Finally, the developed method was successfully used for the analysis of real samples of bio diesel produced from rapeseed oil and its blend with diesel fuel. Samples of biodiesel and biodiesel blends were analyzed directly in an electrochemical cell, while samples with very low concentrations of PY in biodiesel were extracted with water using the proposed simple and fast process.
Citlivá voltametrické metoda pro stanovení antioxidantu pyrogalolu s využitím borem dopované diamantové elektrody
Keywords: Antioxidant; Voltammetry; Pyrogallol; Biofuels; Boron-doped diamond electrode; Antioxidant; Voltamerie; Pyrogalol; Bionafta; Borem dopovaná diamantová elektroda